NILAI MORAL DALAM FILM UANG PANAIK MAHAL KARYA ASRIL SANI DAN HALIM GANI SAFIA - Rahmi Nur Hidayat; Andi Fatimah Yunus; Aswati Asri (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aims to examine and explain the moral values contained in the film Uang Panaik Mahal and its relationship to the culture of the Makassar community. This study uses a descriptive qualitative method with a focus on the disclosure and interpretation of moral valuesrepresented through dialogue and film scenes. The research data are in the form of speech and visual events that reflect moral values, while the main data source is the film Uang Panaik Mahal by Asril Sani and Halim Gani Safia. Data collection techniques were carried out through listening, reading, and note-taking techniques. Researchers watched the film repeatedly to understand the storyline, characters, and socio-cultural context, then noted dialogues and scenes relevant to the focus of the study. Data analysis used the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and drawing conclusions. The results of the study show that the film Uang Panaik Mahal represents the main moral values, namely honesty, being yourself, responsibility, moral courage, independence, humility, and critical attitude. These values are constructed through personal and social conflicts based on local culture, so that this film functions effectively as a character education medium. In addition, this film also serves as a means of reflection and social criticism of the shifting meaning of customs, especially the practice of panaik money, so that it is relevant as a source of character learning based on local wisdom in the context of contemporary society.